2023
DOI: 10.1111/ajco.14000
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell lymphoma patient harboring BCL11B mutations had favorable overall survival

Cunte Chen,
Ling Huang,
Sichu Liu
et al.

Abstract: BackgroundMolecular genetics serve a critical role in constructing risk stratification for hematological malignancies, but T‐cell lymphoma (TCL) still lacks molecular genetic information for supplement risk stratification in predicting the prognosis of TCL patients. In the present study, we characterized the mutation patterns of B‐cell leukemia/lymphoma 11B gene (BCL11B) and its prognostic importance in TCL patients.MethodsBCL11B mutations were characterized based on the data from two datasets, one is from our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(85 reference statements)
0
2
0
Order By: Relevance
“… 3 Our previous study has demonstrated that BCL11B mutation is associated with favorable clinical outcomes in patients with T-cell lymphoma (TCL). 9 Although both T-ALL and TCL belong to T-cell malignancies, there are significant differences between them on the origin of malignant T cells, genetic background, mutation landscape, and treatment options. Therefore, the prognostic value in this study was similar to the published articles on different types of diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 Our previous study has demonstrated that BCL11B mutation is associated with favorable clinical outcomes in patients with T-cell lymphoma (TCL). 9 Although both T-ALL and TCL belong to T-cell malignancies, there are significant differences between them on the origin of malignant T cells, genetic background, mutation landscape, and treatment options. Therefore, the prognostic value in this study was similar to the published articles on different types of diseases.…”
mentioning
confidence: 99%
“…Therefore, the prognostic value in this study was similar to the published articles on different types of diseases. 9 Moreover, a previous report found that BCL11B mutations predict better OS and event-free survival for patients with adult and pediatric T-ALL and may be a potential biomarker for risk stratification in T-ALL 10 ; the relationship between BCL11B mutations and T cells in T-ALL, and the prognostic importance, still remains unclear.…”
mentioning
confidence: 99%